Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1348/000712699161567
|View full text |Cite
|
Sign up to set email alerts
|

Effects of study‐test modality on false recognition

Abstract: Many recent investigations of false memories have generally followed Roediger & McDermott (1995) in using auditory presentation at study and a visual recognition test; the results reveal high rates of false alarms to non‐studied lure words that are associatively related to studied words. We presented lists of words related to critical lure words either auditorially (A) or visually (V); recognition was tested either auditorially or visually, producing four study‐test conditions (AA, AV, VA, and VV). The false r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
3
2

Year Published

2001
2001
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 39 publications
1
29
3
2
Order By: Relevance
“…A more effective strategy for improving memory accuracy will likely require consideration of both encoding and test conditions. Specifically, increasing item-specific processing of list words at study, combined with cueing reliance on this distinctive processing at test, may improve correct recognition while attenuating the DRM illusion (e.g., Maylor & Mo, 1999).…”
Section: Encoding-retrieval Manipulationsmentioning
confidence: 99%
“…A more effective strategy for improving memory accuracy will likely require consideration of both encoding and test conditions. Specifically, increasing item-specific processing of list words at study, combined with cueing reliance on this distinctive processing at test, may improve correct recognition while attenuating the DRM illusion (e.g., Maylor & Mo, 1999).…”
Section: Encoding-retrieval Manipulationsmentioning
confidence: 99%
“…Maylor and Mo (1999) found that auditory study presentation increased true memory and decreased false memory as compared with visual study presentation. Although this finding is in line with some previous studies that have shown greater true memory after auditory than visual study presentation (e.g., Conway & Gathercole, 1987;Gathercole & Conway, 1988), it conflicts with the findings of many others.…”
mentioning
confidence: 93%
“…Smith and Hunt (1998) found that false memories increased following auditory presentation. Maylor and Mo (1999) reported the opposite. Trying to adjudicate between these, Gallo, McDermott, Percer, and Roediger (2001) failed to find a modality effect in one experiment and found increased false memories following auditory presentation in two other experiments (one within and one between subjects) only after discarding the distractor task and only when the test modality (in contrast to the study modality) was visual.…”
Section: Discussionmentioning
confidence: 95%